Do We Love or Hate Tinder? Exploring Implicit Bias in Online Relationships through Story Completion Method - Pilek, Melane; de Saint-Laurent, Constance (AI and Tech in Behavioral and Social Sciences, 2025)
Online dating is increasingly used to form romantic relationships but remains negatively portrayed in public and academic discourse. This study examines implicit representations of relationships initiated through online dating apps and how they compare to traditional and other online methods. In a between-subject experiment using a story completion method, participants (N=367) were presented with scenarios varying by the method of relationship initiation (e.g., in-person, dating apps, online communities). They continued the stories and evaluated the relationships for quality, outcomes, and duration. Results revealed a significant difference in perceived relationship quality. Relationships initiated in online communities were rated more negatively than those formed in person or via Tinder-assisted in-person dates. However, no significant differences were observed in positive evaluations or relationship duration across initiation methods. Notably, Tinder-initiated relationships showed no negative associations, suggesting growing acceptance of Tinder as a platform for forming committed relationships. These findings underscore increasing societal acceptance of online dating while highlighting persistent biases against specific online contexts.